HUBUNGAN TINGGI MUKA AIR TERHADAP BEBERAPA SIFAT FISIK GAMBUT PADA BERBAGAI UMUR TANAMAN KELAPA SAWIT DI DESA KARYA BHAKTI KECAMATAN RANTAU RASAU KABUPATEN TANJUNG JABUNG TIMUR - Nasution, Hasriati; Yusfanety, Yusfanety; Saad, Asmadi; Suryanto, Suryanto (Jambi University, Fakultas Pertanian, Program Studi Agroekoteknologi, 2025)
ABSTRACT Over time, peatland is now changing its function into plantation land such as oil palm plantations on peatland. However, in the management of peatland, it is necessary to pay attention to the nature of peat and soil ir levels, including the regulation of groundwater level. Based on the physical properties of peat soil can be used as an indicator in determining the productivity of oil palm plants on peatlands. Where the important karesteritic in peatland is the water content, soil volume weight, the content of organic matter and the ability to withstand the load of subsidence and non-return dry. Oil palm plants (Elaeis guineensis Jacq.) come from Nigeria, West Africa. Yes, oil palm plants thrive outside their native areas, such as Malaysia, Indonesia, Thailand, and Papua New Guinea. Oil palm plants have an important meaning for the development of national plantations. In addition to being able to create job opportunities and lead to the welfare of the community, palm oil is also a source of foreign exchange for the country and Indonesia is one of the main producers of palm oil. This research was conducted in Karya Bhakti Village, Rantau Rasau District, East Tanjung Jabung Regency. Soil analysis was carried out at the Soil Laboratory of the Faculty of Agriculture, Jambi University. The research was conducted by survey using Proportional Random Sampling. The observed parameters are the height of the water level in the soil, the height of the canal water level, the content of organic matter. Volume Weight, Total Pore Space., peat depth, peat maturity. Each age of palm oil plants, 10 samples were taken at three ages of palm oil plantations 0-5 years, 6- 10 years and eleven years and above. Data interpretation on the age of oil palm oil plants 0 - 5 years, 6 - 10 years and > 11 years was carried out using the Unpaired Middle Value Test on the parameters of soil water level, canal water level height, organic matter content, soil volume weight, peat soil water content. To see the relationship between the height of the peat soil water level with several physical properties of the soil, it was carried out using the Simple Regression Test. The results of the study by using the Unpaired Middle Value Test on the parameters of the groundwater level and the height of the canal water level in palm oil aged 0 - 5 years are clearly different from oil palm plants aged 6 - 10 years and palm oil aged > 11 years. Based on the Linear Regression Test, there is a relationship between the water level of the peat soil and the average water level of the canal in the mustard coconut plant as much as R = 73,33% Keywords: Groundwater Level and Physical Properties of Peat, Palm Oil Plants.